SHOPPING ON SOCIAL NETWORKING SITES: A Study on Facebook Consumers’ Psychological Characteristics - Albert, Albert; Hersinta, Hersinta (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2012)
Saat ini, penggunaan media sosial seperti Facebook dan Twitter menunjukkan peningkatan pesat.  Di  Indonesia,  Facebook  menjadi  salah  satu  media  sosial  dengan  posisi  keempat sebagai negara dengan pengguna terbanyak di dunia. Pada perkembangannya, media social membuka prospek pasar bagi para pemasar di dunia maya atau wirausaha digital. Karena itu, dibutuhkan pemahaman mendalam mengenai karakteristik pembeli online, bagaimana konsumen  menginterpretasikan dan  menerima  stimuli  berupa  pesan  dan  informasi,  yang di tahap selanjutnya dapat mempengaruhi keputusan pembelian. Penelitian  ini bertujuan untuk  memaparkan  faktorfaktor  yang  dapat  mempengaruhi  kelompok  konsumen  usia muda  dalam  berbelanja  di  Facebook.  Faktor  karakteristik  konsumen  online  yang  diteliti difokuskan  pada  faktor  psikologis.  Sebanyak  15  konsumen  pembelanja  online  dalam kelompok generasi Y (usia 2030 tahun) diwawancara dan diobservasi. Hasilnya, terdapat perbedaan  antara  kelompok  pria  dan  wanita,  di  mana  pria  berbelanja  karena  factor keunikan  produk  serta  layanan  (reliabilitas  dan  keamanan  berbelanja).  Sementara  bagi wanita, faktor kenyamanan merupakan hal yang utama. Kata  Kunci:  media  sosial,  facebook,  online  shopping,  perilaku  konsumen. Nowadays,  social  media  like  Facebook  and  Twitter,  showed  increasing  number  rapidly from time to time. In Indonesia, Facebook has become the largest social media, being the fourth  place  in  user  number  in  2012,  comparing  to  other  countries.  As  a  result,  the development  of  social  media  provides a  developing  prospect  for Emarketers  and  digitalentrepreneurs. If Emarketers know the insights on their buyers’ characteristic, they could get  insights  on  how  customers  interpret  and  receive  stimuli  (messages/information), which could affect customers’ decisions. This paper focuses on interpreting factors which affect  young  people’s  online  shopping  in  Facebook,  as  well  as  finding  consumers  online characteristic factors which include cultural, social, personal and psychological factors. In this research, 15 consumers from various online shop in Facebook were interviewed and observed  as informants.  Those  informants  are in  Y  generation  category (age  2030) who had experienced shops online,  male and  female, to  see  if  there any differences between gender in their psychological characteristics. From interviews and observations, male andfemale  have  different  perceptions;  female’s  reasons  to  buy  are  more  because  of convenience, while male’s reasons are mainly because of product uniqueness and customer service  factor, such  as reliability  and  security. Keywords:  social  media,  facebook,  online  shopping,  consumer  behavior. To cite this article (7th APA style):Albert, A. & Hersinta, H. (2012). Shopping on Social Networking Sites: A Study on Facebook Consumers’ Psychological Characteristics. Journal Communication Spectrum, 2(2), 119-132